Performance Anxiety in Western Classical Music: A Malaysian Study - Rita Mardhatillah binti Umar Rauf; Faezah Hamdan (Randwick International of Social Science Journal, 2020)
Although performance anxiety is a common problem in life, there are only a few studies on this subject in Malaysia. This article presents the expansion to the body of literature on this important relationship between performance anxiety in Western Classical Music. Millions of people suffer and may experience from performance anxiety, which commonly called as ‘stage fright’. Worst of all, it may prevent a musician from doing what they enjoy or quit from performing which can effect the career. The knowledge affecting to symptoms and signs anxiety during adolescence among students could help if possible areas can be highlighted for the mediating and prevention on the subjects which may assist Malaysian youths in the university setting so they can control the emotions and reduce the anxiety